ESRA19-0305 Tendencies in the practice of anesthesia for a trauma hospital in COSTA RICA. (30th August 2019) - Fonseca, C
Abstract : Background and aims: We are a reference trauma hospital in Costa Rica with a focus on road and workplace accidents. The anesthetic management of trauma patients has shifted with the advent of regional anesthesia and we have tried to standardize our practice. Our aim was to collect data regarding our daily practice as part of the learning process in research and data collection which we plan to correlate with clinical outcomes in future research. Methods: We searched through our electronic anesthesia records for all patients who underwent surgery during the month of February 2019 and extracted the data regarding primary and secondary anesthetic intervention, the type of surgery and the primary post operative analgesic intervention for those same patients. Results: During February we found 961 electronic records of patients that underwent surgery. Of those 92% underwent surgery for orthopedic procedures and 8% non-orthopedic; the most frequent procedures were ostheosynthesis, arthroscopy and surgical lavage. The most frequent primary anesthetic technique was neuraxial (53%) followed by regional anesthesia (20%) and general anesthesia (19%). Sedation was the most common secondary anesthetic technique (74%) and analgesia was most commonly given through regional anesthesia (71%), followed by intravenous analgesia (19%). Conclusions: The use of ultrasound guided regional anesthesia has become mainstream practice for postoperative analgesia; neuraxial and regional anesthesia are the most common form of primary anesthetic in our hospital, with general anesthesia used mostly for general surgery and neurosurgical procedures. Neuraxial primary anesthesia with sedation and an ultrasound guided regional technique for analgesia was the most common combination.